2007
DOI: 10.1097/01.ico.0000248379.78777.f6
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Fluoroquinolones Against Ocular Bacterial Isolates in São Paulo, Brazil

Abstract: From susceptibility profiles achieved with in vitro testing, the fourth-generation fluoroquinolones may offer some advantages over the currently available fluoroquinolones; however, a combination of the pharmacodynamics and pharmacokinetics of the drug, infection site, and the MIC is needed to predict the in vivo efficacy and best clinical applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
5
25
0
1
Order By: Relevance
“…Considering the meticulous scraping technique followed as a routine in the study, however, the shown high prevalence of CoNS point to CoNS as a main CLMK agent in our environment. Oxacillin resistance was not found among CoNS in the present study, though increasing prevalence has been observed among general eye infections in Brazil (29)(30)(31) . Oxacillin resistance is used to evaluate the resistance of Staphylococcus to beta-lactam agents.…”
Section: Discussionmentioning
confidence: 38%
“…Considering the meticulous scraping technique followed as a routine in the study, however, the shown high prevalence of CoNS point to CoNS as a main CLMK agent in our environment. Oxacillin resistance was not found among CoNS in the present study, though increasing prevalence has been observed among general eye infections in Brazil (29)(30)(31) . Oxacillin resistance is used to evaluate the resistance of Staphylococcus to beta-lactam agents.…”
Section: Discussionmentioning
confidence: 38%
“…15,4045 For in vitro studies, the minimum inhibitory concentrations for 90% of bacterial isolates (MIC 90 ) can be used as relative measure of efficacy for release of antibiotics. All of the CLs, in all testing conditions, released enough moxifloxacin to meet the MIC 90 (0.047 μg/mL) 46 against common and susceptible pathogens over the 24-hour study period.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-four per cent of those who include this in their treatment regime prefer ciprofloxacin. Moxifloxacin has been shown to provide better Gram-positive coverage 23 24. The most common bacteria involved in blebitis are mainly Gram-positive bacteria— Staphylococcus epidermidis, Staphylococcus aureus and Streptococcus pneumoniae —which are consistent with the normal flora on the eye 25 26.…”
Section: Discussionmentioning
confidence: 99%